PENGARUH KESEHATAN MENTAL TERHADAP ETIKA BERKOMUNIKASI DI MEDIA SOSIAL - Arri Handayani; Dini Rakhmawati; Ria Amalia Ria (FOKUS : Kajian Bimbingan dan Konseling dalam Pendidikan, 2026)
This study aims to determine the effect of mental health on communication ethics in social media among students of SMP X. The research employed a quantitative approach with a survey method. The population consisted of 240 eighth-grade students, and 200 of them were selected as the main sample. Data were analyzed using a simple linear regression test assisted by SPSS version 26. The regression equation obtained was Y = 50.575 + 0.415X + ℮, with a tvalue of 3.719 > t-table 1.653 and a significance level of 0.000 < 0.05. These results indicate that mental health has a positive and significant effect on communication ethics in social media. In other words, the better the students’ mental health, the higher their communication ethics in digital interactions. The findings highlight the importance of mental health education and school counseling services in fostering ethical and responsible online communication behaviors.